2018
DOI: 10.1161/jaha.117.008155
|View full text |Cite
|
Sign up to set email alerts
|

Gene Transfer of Engineered Calmodulin Alleviates Ventricular Arrhythmias in a Calsequestrin‐Associated Mouse Model of Catecholaminergic Polymorphic Ventricular Tachycardia

Abstract: BackgroundCatecholaminergic polymorphic ventricular tachycardia (CPVT) is a familial arrhythmogenic syndrome characterized by sudden death. There are several genetic forms of CPVT associated with mutations in genes encoding the cardiac ryanodine receptor (RyR2) and its auxiliary proteins including calsequestrin (CASQ2) and calmodulin (CaM). It has been suggested that impairment of the ability of RyR2 to stay closed (ie, refractory) during diastole may be a common mechanism for these diseases. Here, we explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 58 publications
0
33
0
Order By: Relevance
“…Liu et al recently reported that gene transfer of a mutated CaM (GSH-M37Q), which exhibited a slowed N-terminal Ca dissociation rate and prolonged RyR2 refractoriness, reduced aberrant diastolic Ca 2+ release and alleviated arrhythmias in a calsequestrin-associated CPVT model (20). These findings support the important role of CaM in regulating the RyR2 in the pathogenesis of CPVT.…”
Section: Discussionmentioning
confidence: 71%
“…Liu et al recently reported that gene transfer of a mutated CaM (GSH-M37Q), which exhibited a slowed N-terminal Ca dissociation rate and prolonged RyR2 refractoriness, reduced aberrant diastolic Ca 2+ release and alleviated arrhythmias in a calsequestrin-associated CPVT model (20). These findings support the important role of CaM in regulating the RyR2 in the pathogenesis of CPVT.…”
Section: Discussionmentioning
confidence: 71%
“…We show that the N53I mutation does not alter the affinity of CaM for CaMBD2, neither in the apo nor the Ca 2+ -bound state (Figure 7 and Supplementary Table 4). However, even though the N53I mutation has only a small impact on the Ca 2+ -affinity of CaM alone (30), a reduced Ca 2+ -affinity for the CaM-N53I:CaMBD2 complex was reported (29), owing to an increase in the dissociation rate of Ca 2+ from the complex (42). Single-channel ion conductivity experiments demonstrated that CaM-N53I is not as efficient in closing RyR2 as CaM-WT (28).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the missing hydrogen bonds in the Ca 2+ /CaM-N53I:RyR2-CaMBD2 crystal structure, another significant difference caused by the N53I mutation is an increased Ca 2+ dissociation rate from the N-domain in CaM-N53I, reported previously both in the absence and presence of RyR2-CaMBD2 (30,42). We therefore investigated the dynamics of both CaM-WT and CaM-N53I in absence and in presence of Ca 2+ by NMR.…”
Section: Effect Of the N53i Mutation On Cam Dynamicsmentioning
confidence: 99%
“…Interdisciplinary investigations of this type can elucidate the mechanisms CaM uses to transduces changes in [Ca 2+ ] into modified ion channel function. Such studies will aid understanding how changes in CaM protein sequence can be tolerated, cause or contribute to disease, or potentially even someday enhance physiology [61].…”
Section: Improving Treatment Options For Calmodulinopathiesmentioning
confidence: 99%